Analysis of Single Ended Primary Inductance Converter (Sepic) Efficiency and Losses - Wan Muhammad Firdaus, Wan Sulaiman; Bakri, Hassan; Hamdan, Daniyal (Penerbit Universiti Teknologi Malaysia, 2015)
This paper presents a comprehensive analysis of single-ended primary-inductance converter (SEPIC) efficiency and losses.The target application is a maximum power point tracking (MPPT) for solar photovoltaic application, which demands a high efficiency DC/DC converter topology. Carefully taken care of two predominantly losses in the converter; switching losses and conduction losses, the study presents theoretical justification, simulation analysis and experimental verification.